Physiopathological effects of Escherichia coli O157:H7 inoculation in weaned calves fed with colostrum containing antibodies to EspB and Intimin - Rabinovitz, Bettina Carol; Vilte, Daniel Alejandro; Larzabal, Mariano; Abdala, Alejandro Ariel; Galarza, Roxana Ivon; Zotta, Elsa; Ibarra, Cristina E.; Mercado, Elsa Cristina; Cataldi, Angel Adrian (Elsevier, 2019)
Escherichia coli O157:H7 is responsible for severe intestinal disease and hemolytic uremic syndrome (HUS), a serious systemic complication which particularly affects children. Cattle are the primary reservoir for E. coli O157:H7 and the main source of infection for humans. In this study, we evaluated the ability of transferred maternal colostral antibodies against γ-Intimin C280 and EspB, to protect young weaned calves from E. coli O157:H7 infection. Hyperimmune colostra were obtained by immunization of pregnant cows with a mix of the mentioned antigens. All vaccinated cows mounted a significant IgG response against γ-Intimin C280, and EspB in sera and colostra. Colostrum-fed calves also exhibited high serum IgG titers against γ-Intimin C280 and EspB along with a rise in mucosal γ-Intimin C280-specific IgG antibodies at recto-anal junction and ileum. Additionally, 70 day-old calves received a challenge with E. coli O157:H7 but no reduction in total bacterial shedding or frequency of E. coli O157:H7 excretion from these calves was observed. Most tissue samples showed granulocyte focal infiltrations of the lamina propria and enterocyte erosion. In conclusion, up to the 70th day, the passively acquired γ-Intimin-C280 and EspB-IgG antibodies present in sera and recto-anal mucosa reached a titer insufficient to reduce EHEC O157 shedding and damages of experimentally inoculated young calves.